Evaluation of the outpatient therapeutic program for severe acute malnourished children aged 6-59 months implementation in Dehana District, Northern Ethiopia: a mixed-methods evaluation - Getachew Teshale; Ayal Debie; Endalkachew Dellie; Tsegaye Gebremedhin (BMC, 2022)
Abstract Background In Ethiopia, about 57% of child mortality is associated with acute malnutrition in which the burden is dominant at the rural community. In that regard, the Ethiopian government has been implementing the Outpatient Therapeutic Program (OTP) for managing the uncomplicated sever acute malnutrition among children aged 6 to 59 months at community level by health extension workers. But nothing is known about the implementation status of OTP. Thus, this evaluation aims to evaluate the implementation status of OTP in Dehana district, northern Ethiopia.  Methods A facility-based cross-sectional evaluation with concurrent mixed-method was employed from 1st February to 30th April 2020. A total of 39 indicators were used to evaluate the availability, compliance and acceptability dimensions of the program implementation. A total of 422 mothers/caregivers for exit interview, 384 children's (diagnosed with acute malnutrition) record reviews, nine key informants' interview, and 63 observations were done in this evaluation. A multi-variable logistic regression analysis was used to identify the predictor variables associated with acceptability. Adjusted Odds Ratio (AOR) with 95% confidence interval (CI), and p-value < 0.05 were used to declare statistically significant variables. The qualitative data were tape recorded, transcribed in Amharic and translated into English and finally thematic analysis was done. Results The overall implementation of OTP was 78% measured by availability (87.5%), compliance (75.3%), and acceptability (71.0%) dimensions. Trained healthcare providers, Ready to Use Therapeutic Food (RUTF), Mebendazole, and Oral Rehydration Salt (ORS) were available in all health posts, whereas vitamin A and folic acid were stocked out in some health posts. The health care providers complained that interruption of supplies, work overload and improper usage of RUTF by caregivers were the common challenges of program delivery. Rural residence (AOR = 0.18, 95% CI: 0.09-0.39), knowledge on childhood malnutrition and program services (AOR = 2.27, 95% CI: 1.04-4.97), and had malnourished children previously (AOR = 1.82, 95% CI: 1.01-3.30) were significantly associated with the acceptability of OTP program. Conclusion The overall implementation status of OTP was judged fair. Low achievement was observed on the compliance of health care providers to the standards, and acceptability of program services. Therefore, the program needs great improvement to enhance the outcome of childhood malnutrition management.